Challenges and Opportunities for HIV/AIDS Prevention and Control in Indonesia: A Qualitative Exploration from Health Workers and Stakeholder - Asrina, Andi; Idris, Fairus Prihatin; Gobel, Fatmah Afrianty; Yusuf, Rezky Aulia (Gaceta Médica de Caracas, 2025)
Aim: This study aimed to analyze the challenges and opportunities for HIV/AIDS prevention and control in Bulukumba, Indonesia. Methods: This is a quasi-qualitative study that collects data through observation, in-depth interviews, documentation, and focus group discussions to explore the prevention and control of HIV/AIDS in the Bulukumba district. Primary data were obtained from key informants, namely from the disease prevention and control field of Bulukumba district; ordinary informants are the HIV/AIDS Commission, community leaders, religious leaders, and local government. In addition, data were also obtained from supporting informants, namely field assistants, outreach workers, and representatives of the homosexual community.